Ceiling of the Mukhamandapa (front porch) of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Ceiling of the mukhamandapa (front porch) of the Bhandasar Temple. The innermost circle eight paintings of Jain monks and other parts of the ceiling are adorned with floral motifs. The figure in these paintings is shown wearing a white loin cloth and upper garment, sitting in a yogic posture.